TUBERCULOSIS SURVEILLANCE SYSTEM EVALUATION IN BLITAR DISTRICT: STUDY OF SYSTEM APPROACH AND ATTRIBUTES: Evaluasi Sistem Surveilans Tuberkulosis di Kabupaten Blitar: Studi Pendekatan Sistem dan Atribut - Florentji Adel Benu, Friwanti; Atoillah Isfandiari, Muhammad; Pramono, Endro (Jurnal Berkala Epidemiologi, 2024)
Background: Blitar district was in the last second position in East Java Province, achieving low Tuberculosis recovery and treatment of the national target by 2022. Therefore, it is necessary to support surveillance systems as a prerequisite for providing information as decision-making material. Purpose: to describe the quality of the tuberculosis surveillance system based on its approach and attributes. Methods: This research was an evaluation study design on the tuberculosis surveillance system in 2022. Respondents totaled 19 people. Data was collected by interview using a questionnaire and document study using a checklist. Data was analyzed by comparing the system approach and surveillance attributes to existing guidelines. The data was presented in tables and narratives. Results: Evaluation of tuberculosis surveillance systems based on input, process, and output was available by surveillance guidelines. Evaluation of the surveillance attributes showed that the flexible system has high data quality, high sensitivity, timeliness, and high stability. However, the system is not simple in operation, has low acceptability of the network, and has low positive predictive value because the suspect detection is too loose and not representative. Conclusion: The implementation of the tuberculosis surveillance system has largely been carried out well, supported by several complete surveillance attributes. It is necessary to provide standard operational procedures for recording and reporting, improve coordination with the network to manually and electronically report suspected tuberculosis, and optimize the Mantoux test in children.